Java GUI programming (Canada : Keystone Learning Systems, 2000)
Contents: Introduction to GUI programming, Getting started with AWT, Getting started with SWING, Layout management, Event handling, Text components, General components, Tables, Growing trees, Dialogs and Pop-ups, Graphical programming, Writing applets
Professional programmer, instructor: Eric Rich
Keywords: Java (Computer program language)